2017
DOI: 10.4103/pr.pr_42_17
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plants used by traditional healers in Sangurur, Elgeyo Marakwet County, Kenya

Abstract: Background:Although herbal medical products are still widely used in Kenya, many of the medicinal plants used by traditional medical practitioners (TMPs) have not been documented, despite several challenges that are now threatening the sustainability of the practice.Objective:To document the medicinal plants and healing methods used by TMPs in a region of Kenya with several recognized herbalists for potential research.Materials and Methods:Semi-structured interviews, group discussions, and direct observations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 26 publications
2
35
0
Order By: Relevance
“…This can be linked to the influence of formal education as it was observed that illiterate informants had an upper hand in medicinal plants knowledge as compared to their tertiary level counterparts. Exposure of younger people to modern education and lifestyle has led them to prefer western medical treatment over traditional medicine hence despising medicinal plant treatments compared to those unexposed and uneducated [70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be linked to the influence of formal education as it was observed that illiterate informants had an upper hand in medicinal plants knowledge as compared to their tertiary level counterparts. Exposure of younger people to modern education and lifestyle has led them to prefer western medical treatment over traditional medicine hence despising medicinal plant treatments compared to those unexposed and uneducated [70].…”
Section: Discussionmentioning
confidence: 99%
“…The results between male and female informants were almost equal. The lowest age of informants was 15 and the highest 85 years, with the highest modal class being(66)(67)(68)(69)(70)(71)(72)(73)(74)(75) years, representing 30.8%. The frequency of other age class include, 15-25 (1.3%), 26-35 (3.9%), 36-45 (6.4%), 46-55 (12.8%), 56-65 (19.2%), 66-75 (30.8%), >76-85 (25.6%) (Table 1).…”
mentioning
confidence: 99%
“…Examples of these include paclitaxel, an antitumour drug developed from the bark of T. brevifolia [10], the antimalarial drug artemisinin from Artemisia annua [11], digoxin from Digitalis lanata , atropine from Atropa belladona, aspirin from Filipendula ulmaria, and several other drugs. However, despite the widespread use of medicinal plants in Kenya, several have not been documented [4, 12]. The main aim of this research was to document the medicinal plants used by the Maasai community in Narok County, one of the regions in Kenya whereby the practice of herbal medicine is still widespread for future research.…”
Section: Introductionmentioning
confidence: 99%
“…In Kenya, the decoction or infusion of E. divinorum root are used to induce or augment labor [14]. Fruits are chewed to treat abdominal upsets, skin, kidney and respiratory disorders [15]. In Ethiopia, urine retention is treated by root decoction of E. divinorum [16] while the leaves are used to treat malaria, leprosy, gonorrhea, syphilis and tapeworm [17].…”
Section: Introductionmentioning
confidence: 99%